Pengaruh Jenis Plastik PET, HDPE, PP terhadap Kualitas Asbak melalui Metode Pelelehan dan Pengepressan - Sani Agham, Muhammad Syarif; Hanafi, Tegar; Setiawati, Putri; Riandara, Sinta Yudi; Trisnowati, Eli (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
This study aims to analyze the influence of using various types of plastics, namely Polyethylene (PET), High Density Polyethylene (HDPE), and Polypropylene, on the physical quality of recycled ashtrays made using the melting and pressing method. The ashtray manufacturing process involves mixing recycled plastic with silica sand as a reinforcing material, then melting and molding the mixture using metal molds to achieve a uniform and solid shape. The variation in the type of plastic used aims to determine the differences in the physical characteristics of the resulting product, including density, surface texture, and heat resistance. The research results show that the different types of plastic have a significant impact on the physical quality of the ashtray. The mixture of PET and PP plastics yields the best quality compared to other variations, characterized by a smoother surface, a density of 0.25 g/cm3, and good heat resistance without cracks appearing during testing. Meanwhile, the use of HDPE tends to result in a rougher texture and less-than-optimal adhesion. The addition of silica sand has been proven to increase the overall structural strength and improve the surface smoothness of ashtrays. Overall, this research makes a positive contribution to efforts to reduce plastic waste by repurposing it into functional products. Additionally, the results of this research can also open up opportunities for developing creative products based on recycled materials that are economically valuable and environmentally friendly.